Housing Prices and the Role of Speculation: The Case of Seoul - Donghyun Park; Qin Xiao (Asian Development Bank (ADB), 2009)
Between June 1998 and March 2006, the price index of apartment housing in Seoul, Republic of Korea, more than doubled, while fundamentals such as gross domestic product, wage, and population increased by less than 35%. This study examines the role of a rational speculative bubble in this price surge. We find that unobservable information explains part of the price volatility, and that a rational bubble proxy is a significant driver of prices. However, neither latent information nor rational bubble is enough to explain the recent housing price appreciation, even in conjunction with observable fundamentals.
hdl:11540/1793
Keywords: C13; C52; G12; 330; Speculative bubble; latent information; housing market; Immobilienpreis; Volatilität; Spekulationsblase; Seoul; Südkorea